Peningkatan Pemahaman dan Hasil Belajar Peserta Didik melalui Penerapan Model Pembelajaran Discovery Learning pada Materi Perpangkatan dan Bentuk Akar Kelas IX - Dwi Darmawan, Ahmad Putra; Kertiyani, Ni. Made Intan; Nugroho, Slamet (Mataram University, 2025)
The mathematics learning process at the junior high school level often faces challenges, particularly in conceptual understanding, which affects students’ overall academic achievement. One potential solution to address this issue is the implementation of the Discovery Learning model, which encourages students to independently discover concepts through exploratory learning activities. This study aims to analyze the effectiveness of the Discovery Learning model in improving conceptual understanding and learning outcomes of ninth-grade students at SMP Negeri 13 Mataram on the topic of Exponents and Roots. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through learning activity observations, questionnaires, and mathematics achievement tests. The results showed that the implementation of Discovery Learning successfully enhanced students’ conceptual understanding, as reflected in the increase of the average conceptual understanding score from 60.00 in the pre-cycle (fair category) to 75.50 in cycle I (good category) and 85.75 in cycle II (very good category). Moreover, students’ overall learning outcomes also showed significant improvement, with average scores increasing from 60.25 in the pre-cycle (fair) to 78.00 in cycle I (good) and 88.50 in cycle II (very good). The percentage of students achieving scores above the minimum mastery criterion (KKM) also rose from 35% in the pre-cycle to 60% in cycle I, and 85% in cycle II. Therefore, it can be concluded that the Discovery Learning model is effective in significantly improving students’ conceptual understanding and mathematics learning outcomes.